The basic prerequisites for the professional training and retraining of workers in Kazakhstan - Sharzadin, A.M.; Magrupbekov, E.E. (Publ.KarSU, 2017)
The article presents the main problems of training of workers. The authors have identified and analyzed the requirements of production and the labor market for the quality of training of competitive professional staff. The article describes the problems and tasks of training qualified workforce. Pedagogical approaches that ensure the effective development of the employee in the course of training and retraining are determined. The necessary organizational and pedagogical conditions that meet the requirements of the system of advanced training and retraining of workers have been singled out. Proposals on ensuring the implementation of the priorities for development of vocational education are justified, and measures to improve the current situation are proposed.
Қазақстанда жұмыс мамандарын даярлау жəне қайта мамандандырудың негізгі алғышарттары
Основные предпосылки подготовки и переквалификации рабочих кадров в Казахстане
Keywords: training; workforce; pedagogical approaches; advanced training system; retraining of workforce; vocational education; vocational training